Systematic review of the literature: customer engagement in financial services (Costos y Gestión, 2024)
This study aims to find out about the current factors of Customer Engagement in financial services. For this purpose, a literature review was conducted, applying the PRISMA methodology, analyzing the empirical and theoretical data available from 2014 to 2023, in journals indexed in Scopus. The main findings include the relationship of Customer Engagement and its predictors, taking into account emerging technologies for the formulation of responses and the application of digital marketing strategies focused on strengthening the relationship with the customer. It also highlights the importance of the internal organization to manage customer feedback. In practical terms, it is concluded that future research in each country would be essential to delve deeper into the local particularities that influence customer engagement. This would allow obtaining valuable and specific insights to generate value with customers in each context, optimizing marketing strategies and strengthening engagement in the financial sector.
Keywords: customer engagement; satisfaction, trust; financial services; customer value